2004
DOI: 10.1002/art.20678
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Toll‐like receptors 2 and 4 in rheumatoid synovial tissue and regulation by proinflammatory cytokines interleukin‐12 and interleukin‐18 via interferon‐γ

Abstract: Objective. To study the expression of Toll-like receptor 2 (TLR-2) and TLR-4 and its association with proinflammatory cytokines in synovial tissue from patients with rheumatoid arthritis (RA), osteoarthritis (OA), and healthy individuals.Methods. Synovial tissue specimens from 29 RA patients were stained for TLR-2, TLR-4, and proinflammatory cytokines (interleukin-1␤ [IL-1␤], IL-12, IL-17, IL-18, and tumor necrosis factor ␣ [TNF␣]). The expression of TLR-2, TLR-4, and cytokines as well as the degree of inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
246
0
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(280 citation statements)
references
References 43 publications
(56 reference statements)
18
246
0
12
Order By: Relevance
“…Recently, the adaptor protein MyD88 and its downstream pathway were shown to play a critical role in both spontaneous and carcinogeninduced tumor development [42,43]. Also, in rheumatoid arthritis and psoriasis, several works support evidence of an important role of endogenous TLR ligands that are involved in the induction of inflammation and initiation of diseases [44][45][46]. cPKC inhibitors that inhibit MyD88-dependent inflammatory signals downstream of TLR and IL-1R can be very promising molecules in the treatment of autoimmune inflammatory diseases, as it has been demonstrated with the AEB071 PKC inhibitor on psoriasis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the adaptor protein MyD88 and its downstream pathway were shown to play a critical role in both spontaneous and carcinogeninduced tumor development [42,43]. Also, in rheumatoid arthritis and psoriasis, several works support evidence of an important role of endogenous TLR ligands that are involved in the induction of inflammation and initiation of diseases [44][45][46]. cPKC inhibitors that inhibit MyD88-dependent inflammatory signals downstream of TLR and IL-1R can be very promising molecules in the treatment of autoimmune inflammatory diseases, as it has been demonstrated with the AEB071 PKC inhibitor on psoriasis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that TLR-2 and TLR-4 are expressed in RA synovial tissue (8,16,18) and that this expression was increased compared with that in osteoarthritis or normal synovial tissue (18). TLR-2 was detected by in situ hybridization primarily in cells expressing fibroblast markers (8), while 2-color immunohistochemistry showed that TLR-2 colocalized with CD16ϩ macrophages in the lining (17).…”
Section: Discussionmentioning
confidence: 99%
“…TLR-2 expression was increased on PB monocytes in response to LPS and IL-1␤ (40,41). Further, treatment of monocytes with interferon-␥ (IFN␥) resulted in increased cell surface expression of both TLR-2 and TLR-4 (18,42), and IFN␥ sensitized the monocytes to respond to LPS (43). Although the levels of IFN␥ detected in SF of patients with established RA were low (44), IFN␥ mRNA was present in synovial tissue lymphocytes (45), and it is possible that IFN␥ contributes to sensitizing macrophages to express increased levels of TLR-2 and TLR-4 in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations